Measuring Economic Downside Risk and Severity : Growth at Risk - Wang, Yan; Yao, Yudong (World Bank, Washington, DC, 2014)
Output collapses, and crises are a fact of life. Severe economic downturns occur periodically, and have grave consequences on the poor. The authors propose a new measurement for economic downside risk, and severity: Growth at risk. Similar to the concept of Value at Risk in finance, Growth at Risk summarizes the expected maximum economic downturn over a target horizon at a given confidence level. After providing a taxonomy of growth risks, the authors construct a panel data, set on Growth at Risk for 84 countries, over the period 1980-98. On average, different regional groups experience very distinct Growth at Risk patterns over time. 1) Non-OECD countries experience a higher downturn risk, while OECD countries' downturn risks for both big, and small recessions are the lowest among all groups. 2) East Asia countries, which had been growing faster, had a high Growth at Risk for big downturns, at around six percent, and it rose dramatically at the end of the 1990s. 3) Latin America, and Sub-Saharan Africa also maintained high Growth at Risk for both big, and small recessions through 1980-98. But for Latin America, Growth at Risk for big recessions declined in the 1990s. The authors then investigate the relationship between downside risks, and long-term average growth in a cross-country analysis. They find that higher perceived levels of downside growth risk, seem to be negatively associated with long-term growth. When a country's perceived level of downside growth risk is relatively high, both domestic, and foreign investors might be deterred from making long-term investments in the country, and instead invest elsewhere. The results suggest that prudent, and consistent pursuit of socioeconomic, and political stability, contributes to long-term growth, and that risk management in a broader sense, should be a vital part of the pro-growth, and poverty reduction strategy.